MULTI OBJECTIVE FUZZY LINEAR PROGRAMMING - Muhammad Mefta Eryshady; Oni Soesanto; Muhammad Ahsar Karim (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2014)
Linear programming is a general model that can be used in problem solving the allocation problem of limited resources optimally. The mathematics model of linear programming consists of two function: objective function and constraint function. Based on the number of objective functions, linear programming is divided into two types: Single Objective Linear Programming and Multi-Objective Linear Programming. Multi Objective Linear Programming which values are defined in the scope of fuzzy is called Multi Objective Fuzzy Linear Programming. To find the optimal solution of the problem, firstly it is divided into a linear program with single objective and solved using the simplex method. This research was carried out by using a literature study. The results of this study indicate that the optimal solution of Multi Objective Fuzzy Linear Programming will be decision variable ()x, that are: 12,,...,nxxx which its values if they are substituted into the constraint function, the results will be consistent with the limits of specified| resources, as well as if they are substituted into the objective function, then it will be obtained the optimal solution of all expected purposes.